Factors affecting adherence to evidence-based guidelines in the treatment of URI, sinusitis, and pharyngitis - Andrew Crocker; Richard Alweis; Jorge Scheirer; Shannon Schamel; Tom Wasser; Kris Levingood (Greater Baltimore Medical Center, 2013)
Introduction: Sinus infections, sore throats, and upper respiratory tract infections (URI) are common reasons patients seek medical care. Well-established treatment guidelines exist for prescribing antibiotics in these clinical scenarios, but are not often followed. Objective: The objective of this study is to determine practice patterns related to prescribing antibiotics for sinusitis, URI, and pharyngitis. The main hypothesis is that attending physicians improve their adherence to antibiotic guidelines with a learner present. Methods: A retrospective cohort study was performed on patients treated for URI, sinusitis, and pharyngitis at an ambulatory faculty practice. The use of relevant ICD-9 codes from January 1, 2008 to January 30, 2012 resulted in 1,548 patient encounters which were reviewed for guideline adherence. Univariate analysis and multivariate logistic regression was performed for each outcome variable to determine if they influence antibiotic adherence. Variables studied were physician, presence of a learner, BMI, age, gender, day of the week, month, diabetes, immunosuppression, and COPD. Results: Multivariate analysis showed the statistically significant variables were age (p=0.038) for pharyngitis and provider (p=0.013) for URI. There were no significant findings for sinusitis. Guideline adherence was 24% in patients with pharyngitis, 42% in acute sinusitis, 79% in URI, and 57% overall. Conclusion: Guideline adherence varies depending on the treating physician and decreases when treating younger patients with pharyngitis. The presence of a learner did not improve prescribing habits. The reason for these findings remain unclear, but considerations for improvement could include following antibiotic adherence as a quality measure, giving patients handouts educating them about the impact of overprescribing antibiotics, and further education amongst faculty and residents about adhering to nationally recognized guidelines.